Re-quebros da subjetividade e o poder transformador do samba - Barcelos, Tânia Maia (2006)
This thesis aims at problematizing the contemporaneous subjectivity. In order to achieve this goal, I propose an alliance with the samba, a Brazilian musical gender. I hypothesize that such an alliance can make the subjectivity create strategies of existence, which oppose to hegemonic ways produced by the market of this so called mainstream capitalist regime. Taking into account authors who support an ethical, political and aesthetic perspective of thinking, I work on experimentations I have been through with the samba. I also dialogue with composers, singers and researchers of samba. In these meetings, I point out the intensive features, such as joy, pain and the power of invention which make rhythms of life and the politics of commercializing of affection move. I realize that samba can be a strong ally of the Brazilian subjectivity, especially when it invents run away lines as affirmative resistance strategies. By doing so, the samba can update the ethical vector of the anthropophagous mark of the culture made in the country. This vector can question the identity principle of the disciplinary society still ongoing in Brazil, as well as the flexibility and experimentation principle of the control society soon to be implanted. What it suggests is a devir-samba that crosses the subjectivity with its ability of listening to the body as place for contemporary obstacles inscriptions and of having games and plays with them, providing us all with amusing ways of life which are carriers of a confrontation of such obstacles. It is this transforming ability of the samba that interests me to circumscribe